Inhalation‐Driven Vertical Flutter Triboelectric Nanogenerator with Amplified Output as a Gas‐Mask‐Integrated Self‐Powered Multifunctional System (Adv. Energy Mater. 31/2022). Issue 31 (18th August 2022) - Heo, Deokjae; Song, Myunghwan; Chung, Seh‐Hoon; Cha, Kyunghwan; Kim, Youna; Chung, Jihoon; Hwang, Patrick T.J.; Lee, Jaeheon; Jung, Heesoo; Jin, Youngho; Hong, Jinkee; Kim, Min‐Kun; et al.
Abstract : Triboelectric Nanogenerators In article number 2201001, Jinkee Hong, Min‐Kun Kim, Sangmin Lee and co‐workers report an inhalation‐driven vertical flutter triboelectric nanogenerator (IVF‐TENG) with amplified output. The final prototype of a gas‐mask‐integrated IVF‐TENG demonstrates potential applications as a self‐powered user indicating light, auxiliary power source for commercial sensors and self‐powered respiration/chemical warfare agent sensor.